Posterior parapharyngeal space nerve sheath tumors: Two case reports - SUN Haiyong; YU Aimin; CAO Qing; YAN Qi; JIAO Cheng (Kouqiang hemian waike zazhi)
[Objective:] To explore the feasibility and efficacy of the clinical application of transoral endoscopy in the posterior parapharyngeal space. [Methods:] The clinical data of 2 patients underwent transoral endoscopic nerve sheath tumor resection in the posterior parapharyngeal space were retrospectively analyzed, including clinical symptoms, signs, imaging examinations, pathological types, postoperative complications and their management, and the feasibility of the surgical route was analyzed. [Results:] The tumors were completely resected in both patients. There was no recurrence at 2 years of follow-up. Postoperative complications included: One patient developed Horner's syndrome postoperatively; one patient developed postoperative unilateral vocal fold paralysis. [Conclusion:] Transoral endoscopic surgery for resection of parapharyngeal space tumors is a good minimally invasive route with less bleeding, which is safe and controlled, without cervicofacial incision. However, the long-term efficacy still needs to be further verified by a large number of surgical cases.